Geotechnical investigation and stabilization of soils through limestone powder at Abbottabad, Khyber-Pakhtunkhwa, Pakistan: a cost effective and sustainable approach - Shah, Syed Husnain Ali; Sajjad, Raja Umer; Javed, Asif; Habib, Umer; Ahmad, Faizan; Mohamed, Abdullah (Frontiers in Earth Science, 2023)
This study was designed to determine the geotechnical parameters and stability of soils in the Abbottabad region of Khyber-Pakhtunkhwa, Pakistan. The seven major sites with high population density were selected, covering the entire city, which includes Kalapul, Mandian, Jhangi, Nawan Shahr, Cantonment, Abbottabad Courts and Jinnah Abad. A total of thirty-two (32) boreholes were drilled to a depth of five meters for standard penetration assessment and thirty two (32) field densification tests were performed at the designated sites. The standard penetration tests were carried out at every meter depth of the bore hole for recording penetration resistance, bearing potential and sample collection. Laboratory tests consisting of Atterberg limits, Grain- size analysis, California Bearing Ratio (CBR), Unconfined Compressive Strength (UCS), Direct Shear Box, Proctor Compaction, and Natural Moisture Content (NMC) were conducted according to the ASTM standards on the accrued samples. The values of the performed tests were utilized for soils characterization and inspecting the Liquidity Index, Consistency Index, and Foundation evaluation for quite a number of footings. The results showed that most of the soils of the area belong to the Clay category (CL and A6 class) with excessive values of Plasticity Index (16.9-18.6), Liquidity index (-47.33 to -23.07) and Lower CBR (3% - 6%), Angle of Internal Friction (15 degree-20 degree), UCS (79 kPa-121 kPa), Dry Density (15.13 kN/m3-17.66 kN/m3) and Bearing Capacities, except the parts of Kalapul area, which belonged to the GP (poorly graded gravels) category with significant geotechnical properties. Based on the obtained results, we found that the land in the vicinity needs significant improvement before construction. For this purpose, various concentrations of limestone (12.5% and 25%), which is heavily mined in the area, were used as an additive. The results showed that the addition of limestone powder produced a significant improvement in all investigated properties and made the soft soil suitable for construction, in addition to any extended stabilization measures. The main reason for this improvement is the presence of more dense and lower water-absorbing minerals in the limestone than in the ground, or mineralization reactions between them.